2020
DOI: 10.1111/ppl.13062
|View full text |Cite
|
Sign up to set email alerts
|

Leaf mass area determines water use efficiency through its influence on carbon gain in rice mutants

Abstract: Saving water and enhancing rice productivity are consensually the most important research goals globally. While increasing canopy cover would enhance growth rates by higher photosynthetic carbon gain, an accompanied increase in transpiration would have a negative impact on saving water as well as for sustainability under water‐limited conditions. Increased water use efficiency (WUE) by virtue of higher carbon assimilatory capacity can significantly circumvent this trade‐off. Here, we report leaf mass area (LMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…This result suggests that stomatal conductance had better performance when rice height was short [ 45 , 46 ], whereas net photosynthesis and water-use efficiency were contained together in PC-3 in both drought stress and drought stress plasticity conditions with the same polarity. This suggests that water use efficiency could be increased by improving carbon assimilation [ 47 , 48 ]. Stomatal traits such as upper stomatal density, upper guard cell width, lower guard cell length, and lower maximal pore area were combined in PC-2 under both drought stress and drought stress plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that stomatal conductance had better performance when rice height was short [ 45 , 46 ], whereas net photosynthesis and water-use efficiency were contained together in PC-3 in both drought stress and drought stress plasticity conditions with the same polarity. This suggests that water use efficiency could be increased by improving carbon assimilation [ 47 , 48 ]. Stomatal traits such as upper stomatal density, upper guard cell width, lower guard cell length, and lower maximal pore area were combined in PC-2 under both drought stress and drought stress plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Horike et al (2021) , WUE i of five shrub species covaried with LMA under drought stress. LMA differences explained WUE 13C variance across rice mutants through its influence on carbon gain ( Reddy et al 2020 b ). A study by Medrano et al (2009) also reported a positive correlation between WUE i and LMA in Mediterranean herbs and shrubs.…”
Section: Leaf Anatomy and Plant Crown Architecturementioning
confidence: 99%
“…Likewise, C 4 forage crops will also have a decisive role in future climatic conditions, having higher carbon-fixation efficiency, water-use efficiency (WUE) and biomass production, and lower photorespiration and N 2 O and methane production, than C 3 plants (Ning et al 2020;Reddy et al 2020;De Haan et al 2021). Therefore, both C 4 and perennial forage crops have great potential to adapt to fluctuating climatic situations.…”
Section: Introductionmentioning
confidence: 99%